2016
DOI: 10.1111/pai.12515
|View full text |Cite
|
Sign up to set email alerts
|

Formula with long‐chain polyunsaturated fatty acids reduces incidence of allergy in early childhood

Abstract: Background Allergy has sharply increased in affluent Western countries in the last 30 years. N-3 long chain polyunsaturated fatty acids (n-3 LCPUFAs) may protect the immune system against development of allergy. Methods We prospectively categorized illnesses by body system in a subset of 91 children from the Kansas City cohort of the DIAMOND (DHA Intake and Measurement of Neural Development) study who had yearly medical records through 4 years of age. As infants, they were fed either a control formula withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 31 publications
3
47
0
1
Order By: Relevance
“…Clinical studies demonstrate that consuming formula with DHA and ARA contributes to the development of a more mature immune system [58,59], improves immune responses to dietary allergens [60], may reduce the risk of allergic diseases in the first year of life [61], and may reduce the risk of upper respiratory infections and diarrhea [33,62].…”
Section: Lcpufa In Infant Formula: Clinical Results and Future Directmentioning
confidence: 99%
“…Clinical studies demonstrate that consuming formula with DHA and ARA contributes to the development of a more mature immune system [58,59], improves immune responses to dietary allergens [60], may reduce the risk of allergic diseases in the first year of life [61], and may reduce the risk of upper respiratory infections and diarrhea [33,62].…”
Section: Lcpufa In Infant Formula: Clinical Results and Future Directmentioning
confidence: 99%
“…Sin embargo, sus precursores, los ácidos grasos esenciales linoleico y α-linolénico, se encuentran en bajas proporciones a nivel cerebral. Asimismo, también se han atribuido funciones inmunomoduladoras a los ácidos grasos poliinsaturados de cadena larga (6).…”
Section: Avances En La Calidad De La Fracción Lipídica áCidos Grasos unclassified
“…They found fewer medically documented allergic illnesses in the first 3 years of life in children receiving formula with compared with without LCPUFA. Similarly, the authors recently reported fewer medically documented allergies in the first 4 years of life with formulas containing DHA (0.32%–0.96%) and ARA (0.64%) compared with formula without LCPUFA [103]. When the authors assessed predictors of skin allergy and wheeze/asthma, we found an interaction with maternal allergy: LCPUFA protected against skin allergy in children of women who did not report allergy and against wheezing/asthma in children of women who reported allergy [103].…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, the authors recently reported fewer medically documented allergies in the first 4 years of life with formulas containing DHA (0.32%–0.96%) and ARA (0.64%) compared with formula without LCPUFA [103]. When the authors assessed predictors of skin allergy and wheeze/asthma, we found an interaction with maternal allergy: LCPUFA protected against skin allergy in children of women who did not report allergy and against wheezing/asthma in children of women who reported allergy [103]. There is a need to determine when in development LCPUFA is important for reducing allergy [104106].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation